1983
DOI: 10.1039/p19830000871
|View full text |Cite
|
Sign up to set email alerts
|

Studies of terpenoid biosynthesis. Part 29. The cleavage of the sterol side chain in the biosynthesis of demethoxyviridin

Abstract: The structures of a group of C6 and C7 alcohols obtained from Nodulisporium hinnuleum have been elucidated. When biosynthesized from [2-14C]me~alonic acid they have been shown to have a specific activity consistent with a common origin with their co-metabolite, demethoxyviridin. The number of [2-2H2] mevalonoid hydrogen atoms which were incorporated suggests that they were formed initially at the aldehyde oxidation level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The number and location of the hydrogen atoms originating from acetate and the 2-, 4-, and 5-positions of mevalonate were determined by a combination of 3H : 14C ratios in radioisotope feeding studies and 2H N M R studies. This work supported the intervention of a lanostane (35) rather than a cycloartenol (39) precursor, which would have been characteristic of plant steroid biosynthesis. The loss of a hydrogen atom from C-15 suggested that the removal of the C-14 methyl group followed a similar pathway to that found in other steroid biosyntheses.…”
Section: Biosynthesissupporting
confidence: 59%
See 1 more Smart Citation
“…The number and location of the hydrogen atoms originating from acetate and the 2-, 4-, and 5-positions of mevalonate were determined by a combination of 3H : 14C ratios in radioisotope feeding studies and 2H N M R studies. This work supported the intervention of a lanostane (35) rather than a cycloartenol (39) precursor, which would have been characteristic of plant steroid biosynthesis. The loss of a hydrogen atom from C-15 suggested that the removal of the C-14 methyl group followed a similar pathway to that found in other steroid biosyntheses.…”
Section: Biosynthesissupporting
confidence: 59%
“…The 13C NMR spectroscopic coupling pattern of wortmannin (34) biosynthesized from [ 1 ,2-13C2]acetate was also in accord with a triterpenoid biosynthetic pathway. 30 The incorporation of [3H]lanosterol (35) into viridin31 and w ~r t m a n n i n ~~ has been described. These studies also served to confirm the absolute stereochemistry of this series of compounds.…”
Section: Biosynthesismentioning
confidence: 99%
“…spectra of the ( + )-methyl mandelate ester^. '^' If either (6R)-[6-2Ht]-or (6S)-[6-2H,]-~-glucose was incorporated into ribostamycin (265) by Streptomyces ribosidrJcus, the two hydrogen atoms at C-2 of the deoxystreptamine moiety were stereospecifically labelled. 287 In addition, the 6(pro-6R)hydrogen of the glucose is stereospecifically incorporated into the neosamine C unit, but the corresponding pro-S-hydrogen is lost.…”
Section: Incorporation Of Primary Precursors With Stereospecijic Deut...mentioning
confidence: 99%
“…To gain further insight into the biosynthesis of demethoxyviridin from lanosterol, Hanson et al identified a group of ergosterol side-chain-derived C6 and C7 alcohols sharing a common origin with demethoxyviridin. This suggested that the removal of the sterol side chain during demethoxyviridin biosynthesis occurs between C20 and C22, in a pathway analogous to the sterol side-chain cleavage during the biosynthesis of steroid hormones in mammalian cells 18 , 19 . Despite these advances, the genetic basis for the biosynthesis of furanosteroids has remained elusive.…”
Section: Introductionmentioning
confidence: 99%